Mangasarian-type Higher-order Duality in Multi-objective Programming with Complementarity Constraints (European Journal of Pure and Applied Mathematics, 2026)
This article establishes Mangasarian-type second and higher-order dual formulations for a multi-objective mathematical program with complementarity constraints (MMPCC) by utilizing μ-stationary conditions. Subsequently, we present several duality theorems for the second and higher-order duals of (MMPCC) under υ-bonvexity assumptions. These results are further illustrated with appropriate examples.
Keywords: Multi-objective programming, mathematical programs with complementary constraints; generalized convexity; second-order and higher-order type I duality.